Reduction of atrial fibrillation burden by pulmonary vein isolation leads to a decrease of CD11b expression on inflammatory cells. Issue 3 (10th January 2017) - Tarnowski, Daniel; Plichta, Lina; Forkmann, Mathias; Quick, Silvio; Ulbrich, Stefan; Heidrich, Felix Matthias; Wiedemann, Stephan; Christoph, Marian; Poitz, David Maximilian; Wunderlich, Carsten; Ibrahim, Karim; Strasser, Ruth H; et al.
Abstract: Aims: It is hypothesized that inflammation could promote structural and electrical remodelling processes in atrial fibrillation (AF). Atrial infiltration of monocytes and granulocytes has been shown to be dependent on CD11b expression. The aim of this study was to investigate whether treatment of AF by pulmonary vein isolation (PVI) may lead to reduced inflammation, as indicated by a decrease of CD11b expression on monocytes and granulocytes. Methods and results: Flow-cytometric quantification analysis and determination of systemic inflammatory markers of peripheral blood were performed in 75 patients undergoing PVI 1 day before and 6 months after PVI. The extent of activation of monocytes and granulocytes was measured by quantifying the cell adhesion molecule CD11b. The mean expression of CD11b on monocytes (20.9 ± 2.5 vs. 10.2 ± 1.4; P < 0.001) and granulocytes (13.9 ± 1.6 vs. 6.8 ± 0.5; P < 0.001), as well as the relative count of CD11b-positive monocytes ( P < 0.05) and CD11b-positive granulocytes ( P < 0.01) were significantly reduced when comparing the identical patients before and 6 months after PVI. Systemic inflammatory parameters showed only a declining tendency after 6 months. Patients with unsuccessful PVI and ongoing AF on the day of follow-up showed no decrease in CD11b expression. Conclusions: A significant reduction of CD11b expression on monocytes and granulocytes, as a sign of reduced cellular inflammation, was achieved by treatment of AF using PVI. These data strongly support that AF is not only a consequence of but also a cause for inflammatory processes, which, in turn, may contribute to atrial remodelling.